2012
DOI: 10.1007/s00382-012-1500-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean model resolution on CCSM climate simulations

Abstract: The current literature provides compelling evidence suggesting that an eddy-resolving (as opposed to eddy-permitting or eddy-parameterized) ocean component model will significantly impact the simulation of the large-scale climate, although this has not been fully tested to date in multi-decadal global coupled climate simulations. The purpose of this paper is to document how increased ocean model resolution impacts the simulation of large-scale climate variability. The model used for this study is the NCAR Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
265
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(285 citation statements)
references
References 54 publications
15
265
3
2
Order By: Relevance
“…In contrast, when the ocean model uses a coarse grid (1.0° or coarser), the opposite is found (Kirtman et al 2012). These results point to the high possibility that frontal-and mesoscale air-sea interactions are poorly represented in CMIP5 models, consistent with the CMIP3 analysis by Maloney and Chelton (2006), with potential consequences for the fidelity of simulations of the hydrological cycle.…”
Section: The Global Hydrological Cyclementioning
confidence: 63%
“…In contrast, when the ocean model uses a coarse grid (1.0° or coarser), the opposite is found (Kirtman et al 2012). These results point to the high possibility that frontal-and mesoscale air-sea interactions are poorly represented in CMIP5 models, consistent with the CMIP3 analysis by Maloney and Chelton (2006), with potential consequences for the fidelity of simulations of the hydrological cycle.…”
Section: The Global Hydrological Cyclementioning
confidence: 63%
“…S2). Kirtman et al (22) showed that the Arctic warming is associated with significant losses of sea ice in the simulation with high resolution of sea ice and ocean model components using CCSM3.5 (the forerunner to CCSM4). DeWeaver and Bitz (23) suggested the simulation of Arctic sea ice and surface winds changes significantly when the resolution of the atmospheric model component is increased.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…especially in controlling the heat transport of boundary currents. For example, moving from 1° to 0.25° (eddy-permitting) resolution in the modern-day climate results in an enhanced western boundary current heat transport (Delworth et al, 2012), and this effect can cause substantially lower Arctic sea ice coverage (Hutchinson et al, 2015;Kirtman et al, 2012). Moving from 3° to 1° ocean resolution, while still not permitting eddies, would improve the representation of boundary currents and their associated 5 impacts on gateway transitions.…”
Section: Hypotheses 15mentioning
confidence: 99%